Pertumbuhan Tanpa Batas: Transformasi Pembelajaran Sepanjang Hayat Melalui Integrasi Pendamping Edukasi yang Pervasif - Chow, Teng Poh; Nyoman, Parwati Ni; Ketut, Agustini; Made, Tegeh I (Kolaborasi Masyarakat, 2025)
“You don’t really understand something until you learn it in more than one way.” – Marvin Minsky. Pervasive learning is transforming educational paradigms by enabling adaptive, continuous, and personalized learning experiences beyond traditional classrooms. This study proposes an innovative framework for a Pervasive Educational Companion that seamlessly integrates into daily activities to support lifelong learning. Focusing on adult learners as the primary users, the research emphasizes the need for flexibility, autonomy, and adaptability in learning processes. Through literature review, mixed-methods analysis, and empirical validation, the study highlights the significance of personalization, adaptability, and systemic integration for effective learning environments. Findings indicate that elements such as gamification and virtual reality substantially enhance learner motivation and engagement. The proposed system provides real-time feedback, adaptive learning pathways, and contextual resources to improve learning retention and efficiency. Key challenges—including technological barriers, digital inequality, and pedagogical evolution—are also discussed. This framework aims to build an inclusive and transformative pervasive learning ecosystem empowered by AI and IoT, fostering sustainable individual growth through lifelong learning.